Monday

December 22, 2014

December 22, 2014

Posted by **Mia** on Tuesday, November 27, 2012 at 6:35am.

- Mathh -
**Reiny**, Tuesday, November 27, 2012 at 9:28am√((-9)(-4))

= √36

= 6

or

√((-9)(-4))

= (√-9)(√-4)

=(3i)(2i)

= 6i^2

= 6(-1)

= -6

so what do you think?

**Answer this Question**

**Related Questions**

math,correction - Simplify by combining like terms. Problem #32 radical (63) - 2...

math , help,algebra - i am up to this point in my problem but i don't know what ...

math,correction - Can somoene helpme plz... Simplify radical 7 * radical 14 ...

math - in the question 6radical x +3 radical y -2radical y +3 radical x -radical...

Algebra - I'm adding 2(radical 50) + 12 (radical 8). I began by breaking the ...

Math - Symplify (radical x/8) is the answer x (radical 2)/4 i put it to be (x/2...

Algebra 1 - Am i on the right track? radical of 3 times radical of three= ...

trigonometry - Simplify and write in standard form. 1.) (radical 3 + i radical ...

algebra - 3 radical x - 4 radical y divided by 3 radical x - 2 radical y = ( i ...

math - Can somebody please help me with this problem? This is the index-„³ 5 6^-...